2019
DOI: 10.3390/v11030214
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Histopathologic, and Immunohistochemical Characterization of Experimental Marburg Virus Infection in A Natural Reservoir Host, the Egyptian Rousette Bat (Rousettus aegyptiacus)

Abstract: Egyptian rousette bats (Rousettus aegyptiacus) are natural reservoir hosts of Marburg virus (MARV), and Ravn virus (RAVV; collectively called marburgviruses) and have been linked to human cases of Marburg virus disease (MVD). We investigated the clinical and pathologic effects of experimental MARV infection in Egyptian rousettes through a serial euthanasia study and found clear evidence of mild but transient disease. Three groups of nine, captive-born, juvenile male bats were inoculated subcutaneously with 10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 46 publications
7
53
0
Order By: Relevance
“…MARV-inoculated animals showed histopathology like that observed in prior experimental infection studies 10 . Immunohistochemistry with a pan-filovirus antibody suggested that MARV was present in mammary glands and testes, despite the lack of histopathological lesions in these organs.…”
Section: Inoculation Of Bats With Marv and Ebov Results In Detectablesupporting
confidence: 72%
See 2 more Smart Citations
“…MARV-inoculated animals showed histopathology like that observed in prior experimental infection studies 10 . Immunohistochemistry with a pan-filovirus antibody suggested that MARV was present in mammary glands and testes, despite the lack of histopathological lesions in these organs.…”
Section: Inoculation Of Bats With Marv and Ebov Results In Detectablesupporting
confidence: 72%
“…The most abundant group in this set comprised genes related to mitochondria (20 genes), followed by genes involved in the vascular system (19), innate immunity (16), tissue regeneration and apoptosis (15), macrophages (13), inflammation (10), metabolism and fatty-acid oxidation (8), T cells (4), complement system (2), digestion (5), and toxin processing (3).…”
Section: Evolutionarily Divergent Bat Genes As Tools For Understandinmentioning
confidence: 99%
See 1 more Smart Citation
“…Current data suggest that the classical pathology caused by strong activation of the immune system in response to viral infection that is seen in humans and laboratory animal models does not occur in bats 37,47 . The lack of pathology observed in bats is likely due to a combination of differences in viral tissue tropism and host immune responses 48 . Viral replication and shedding in bats in combination with an apparent lack of disease may allow for the efficient maintenance and dissemination of viruses.…”
Section: Innate Bat Immunitymentioning
confidence: 99%
“…[18][19][20] Further, infecting ERB bone marrow-derived dendritic cells (BMDCs) failed to increase inflammatory gene expression, while experimental MARV infections of ERBs produced minimal, if any, gross histological signs of inflammation, even in tissues with highest viral loads. 3,5,6,21,22 The culmination of these data led us to hypothesize that ERBs have indeed developed a system of disease tolerance to MARV. However, significant testing of this hypothesis has so far been limited to immortalized cell lines, ex vivo tissue culture infections, or genomic approaches that cannot reproduce or examine the complexity and context of an immune response in a whole animal, which to our knowledge remains uncharacterized at a broad transcriptional level for any bat reservoir of a human-pathogenic virus, including ERBs infected with MARV.…”
Section: Introductionmentioning
confidence: 99%